ECO-FEAR AND ECO-TERROR IN FILMS: A STUDY OF CHANGING PARADIGMS IN INDIAN CINEMA - Mondal, Rangalal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cinema and movies always work as a tool of awareness. Indian cinema, especially the Bollywood movie industry is changing its paradigm from the traditional romanticized catchup and family drama to socio-political and environmental awareness. The young and new generation filmmakers’ interests fall on the impending issues rather than so-called traditional issues. They take cinema as a tool to raise sensitive issues as only this medium can rapidly raise awareness among the mass population. Except for the other issues, the ecological issues also become the main subject of their movie. Nila Madhab Panda, the award-winning director uses cinema as a tool of awareness. His movie Kaun Kitney Paani Mein (2015) is the best example of environmental awareness. This film points out very critical issues of water crisis of two villages- Upri and Bairi. His movie highlights how unskilled and mismanagement can lead to the brink of shortage and scarcity. Another director, Aparnaa Singh points out the consequence of fatal disease due to the chemical reaction in groundwater in her movie Irada (2017). The paper attempts to emphasize how cinema can take as a tool of environmental awareness for the mass population analysing the visual portrayal in detail with the help of two theories- Agenda Setting Theory and Walter’s Narrative Paradigm. It also aims to focus on changing paradigm of the contemporary Indian cinemas dealing with the ecological conscience.